Histomorphochemical changes in the mediastinum testis of buffalo bull in different seasons - ASLAM, BEENISH; BANSAL, NEELAM; UPPAL, VARINDER; GUPTA, ANURADHA (The Indian Journal of Animal Sciences, 2018)
The present study was conducted on the mediastinum testis of 24 adult buffalo bulls collected from the abattoir, Dera Bassi (Chandigarh) immediately after sacrifice during summer, autumn, winter and spring seasons. The tissue samples were fixed in 10% neutral buffered formalin, processed by acetone benzene technique and stained for histological and histochemical studies. For histoenzymic studies, fresh tissue samples were subjected to cryostat sectioning and incubated in different substrates to demonstrate the sudanophilic lipids and various enzymes. The results revealed that the medistinum testis comprised rete testis and large blood and lymph vessels. The rete tubules were lined by simple cuboidal to columnar type epithelium in all the seasons except in summer where it showed stratification. There was decrease in the tubular size of rete testis but the collagen, elastic and reticular fibres and neuronal elements were more during autumn and winter than summer and spring. The reaction of acid and neutral mucopolysachharides, Sudanophilic lipids and basic proteins were moderate to strong in the mediastinum testis during winter and autumn, moderate in spring and weak in summer seasons. The activity of phosphatases and dehydrogenases was weak to moderate during winter and weak in summer. The alterations of various histochemical and histoenzymic activites in the mediastinum testis may be correlated with the reproductive status of the animal with respect to the season.